Studies of the mycoflora of barley during storage and its relation to mycotoxin contamination : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Microbiology at Massey University - Lee, Wen Shya (Massey University, 1986)
Much of the economic loss occurring during storage of barley grain is that due to fungal deterioration. In addition, the development of mycotoxins during storage may result in contamination of animal feedstuffs. In this study barley from samples obtained at harvest, from commercial silos after 5 and 9 months' storage, from farm silos after 5 months' storage and from laboratory-stored samples held at 4°C and at ambient temperature were subjected to various fungal isolation techniques. These techniques were designed to provide information on the total viable counts of the whole grain and of the outside and inside surfaces of the husks and caryopses. Isolates of Aspergillus flavus were screened for toxigenicity and the barley itself was subjected to multimycotoxin analysis. To investigate levels of contamination, dilution plating of supernatants from the inner and outer parts of grains were examined. Differential viable counts revealed wide variations between samples at harvest and after storage with most contamination on the outer surface. "Clean" grain showed higher outer than inner counts, but for mouldy grains inside counts were greatly increased. It was concluded that inside counts give a better indication of grain condition. Commercially-stored grain showed a marked decrease in viable counts over time, as did the laboratory-stored grain although those held at 4°C showed a smaller decrease. In contrast, the farm-stored grain continued to yield high viable counts. These counts could be related to storage conditions. Amongst the genera isolated from dilution plates, Alternaria was the most frequent and persistent, whilst others, including Cladosporium and Fusarium, showed falling levels over the period of investigation. The genera Penicillium and Aspergillus showed rising frequencies with storage and were predominant in mouldy samples. Microscopic examination and culturing of caryopsis sections and husk surfaces revealed the significance and distribution of various genera. Alternaria was found in all fractions whereas Penicillium was completely absent from grain at harvest, later appearing on the outer husk and finally on the inner husk after prolonged storage at ambient temperature. Microscopy of stained caryopsis sections showed hyphae only in those from mouldy grain. Microscopy of stained husks revealed hyphae on and in both husk surfaces of all grains, with a greater abundance on the inner surface and in mouldy husks. S.E.M. observations confirmed these findings and established the adherence of spores and hyphae to grain structures and their rough surfaces. Some hyphal fragments associated with the grain can cause mycotoxin contamination. Loosely-attached hyphae were examined using membrane filtration and micro-manipulation techniques. It was found that whilst total levels of hyphal fragments showed little decrease during storage, their viability dropped considerably. For silo- and laboratory-stored grain, the viability dropped from over 20% to 5%. In contrast, over 45% were viable in a mouldy sample. Of the fungal species isolated, species of the Aspergillus flavus group were screened for aflatoxin production using coconut agar fluorescence. Positive isolates ranged from 3% for farm-stored grain to 25% of those from grain at harvest. Selected A. flavus isolates were cultured on moist barley which when analysed for aflatoxin gave identical results to those from the coconut agar. A multimycotoxin technique was used to screen 14 barley samples for aflatoxins, citrinin, ochratoxin, T-2 toxin and zearalenone. Only one obviously-mouldy sample proved positive for aflatoxin, citrinin and ochratoxin. It appears that although A. flavus and other potentially toxigenic fungi can be regularly isolated from barley grains, only in exceptional circumstances are they of significance in relation to mycotoxin contamination of stored grain.
Keywords: Barley grain storage; Mycotoxins; Aspergillus flavus; Stored grain